SYNTHESIS AND POLYCYCLIC AROMATIC HYDROCARBONS BINDING STUDY OF PROTONATED POLYAZA MACROCYCLES - Kumarasinghe, W.M.D.M; Fernando, I.R. (International Conference of Multidisciplinary Approaches, 2019)
Polycyclic aromatic hydrocarbons (PAHs) are a group of hydrogen and carbon-containing organic compounds which consist of two or more fused aromatic rings. The PAHs originate from the natural- as well as anthropogenic- sources are accumulated in the environment while causing adverse effects on the human health. Among the chemical methods that are employed to detect and sequester the PAHs, the host-guest complex formation between PAHs ‘guests’ and macrocyclic ‘hosts’ are yet to be explored. Therefore, the main objective of this research project was to develop a donor-acceptor interaction driven host-guest chemistry-based method to scavenge a range of electron-rich PAH ‘guests’ using a series of electron-deficient protonated polyaza macrocyclic ‘hosts’ which possess different cavity sizes. The synthetic design of the electron-deficient protonated polyaza macrocyclic ‘hosts’ starts with the synthesis of a series of macrocycles of Schiff-bases (MSB 1-3) by reacting a dialdehyde, terephthalaldehyde with three different terminal diamines, diethylenetriamine, triethylenetetramine and tetraethylenepentamine, followed by the reduction of MSBs with NaBH4 and the protonation with HBr to obtain the corresponding polyaza macrocycles (PAZ 1-3) and protonated polyaza macrocycles (PPAZ 1-3), respectively. In the Fourier transform infrared spectrum of MSB 1, the disappearance of a –C=O peak of terephthaldehyde around 1730 cm-1 and the appearance of a new –C=N peak around 1640 cm-1 confirmed the macrocyclic Schiff-base formation. The peaks at H 8.297 (–CH=N), 7.537 (aromatic H), 3.797 (–CH2-N=), 3.005 (–CH2-NH) ppm of the Proton Nuclear Magnetic Resonance Spectra of MSB 1 further confirmed the cyclization. Preliminary qualitative binding studies between PPAZ 1 with PAHs — naphthalene, anthracene and phenanthrene — were monitored using UV-visible spectroscopy and results suggest that some of the PAHs in the organic layer transferred to the aqueous layer. In order to confirm the host-guest inclusion complex formation in aqueous layer, further studies need to be carried out.
Keywords: polycyclic aromatic hydrocarbons, host-guest chemistry, macrocyclic schiff-bases, polyaza macrocycles, inclusion complexes